Viability of solar photovoltaic system for rural electrification in Nigeria - Alkali, A.B.; Abdulrahim, A.T.; Mustapha, B.M. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2004)
Electricity availability in rural areas is identified as one of the social amenities that drastically reduce poverty problem by bridging the gap between the rural area and the urban centres. A suitable, cheap and reliable source of power, which could be minimally maintained and manipulated, is necessary to transform the life of an average rural family. This paper focuses on the solar system as a possible alternative to meet the above need. The paper presents a solar photovoltaic (PV) design and cost analysis for a typical single bedroom apartment.  It also recommends integration of renewable energy into national strategies to cope with the economic and technical uncertainties that may constrain the supply of conventional energy.